Il tempo non è uguale per tutti. Come il Covid-19 ha cambiato l’accelerazione sociale nella società neoliberista - Stefano Tomelleri (SocietàMutamentoPolitica: Rivista Italiana di Sociologia)
This paper is a personal attempt to rethink critically the social impact of the Covid-19 pandemic, trying to discuss about some changes, which came out in that tragic period, in the way of living time and space. There are several ways in which the COVID-19 pandemic has affected these two main structural dimensions of society and the response strategies used by people, groups, and social organizations, depending on the geographical area. There are trends that have had a highly differentiated impact, which have shown that the concept of time is not the same for everyone. Other trends have had a transversal impact, reconfiguring the ideas of present and future. Precariousness and uncertainty, that coincide with an existential specific condition of our contemporary, now take on a new meaning. Before the pandemic, the neoliberal development model seemed to have no alternative. Now, the possibility of an alternative model is imaginable, not only for the critics of it, but also for a large part of public opinion, which now even considers it necessary. The possibility of an alternative becomes concrete and achievable due to the impact that the Covid-19 pandemic has had on the structural dimensions of time and space in social life.